Response of cocoa (Theobroma cacao L.) seedlings to folia fertilizer application and fertigation - Yeboah, S. (Kwame Nkrumah University of Science and Technology, 2023)
The production of quality and vigorous seedlings is important for sustainable cocoa production. A greenhouse nursery study was conducted in 2019/2020 at CRIG to assess the effects of foliar fertilizer application and fertigation on soil chemical properties, nutrient uptake and growth of cocoa seedlings. The study was 4x3 factorial experiment, laid out in completely randomized design with 13 treatments and three replicates. Two liquid fertilizers (NPK 24:17:18 and NPK 10:10:10) and two granular fertilizers (ammonium sulphate and calcium nitrate) were applied at 42, 84 and 126 mg N per pot. The liquid fertilizers were applied through foliar spraying, while the granular fertilizers were applied through fertigation. Topsoil was collected from an uncultivated land at CRIG and used for the experiment. The soil was processed and analyzed to assess the pre and post experiment physico-chemical properties using standard protocols. Growth and nutrient uptake by the cocoa seedlings were determined using standard procedures. Data from the experiment were subjected to ANOVA and Pearson’s correlation analysis. The initial topsoil was sandy clay loam; had pH of 7.04; 1.94 % organic C; 0.21 % total N; 8.01 mg kg-1 available P; and 0.32 cmolc kg-1, 2.41 cmolc kg-1, 10.20 cmolc kg-1 exchangeable K, Mg, Ca respectively. The initial topsoil had normal levels of physico-chemical characteristics suitable for cocoa cultivation, except available P which was lower than the threshold level of 20 mg kg-1. The study showed that high ammonium sulphate fertigation rate (126 mg N per pot) significantly reduced soil pH from 7.04 to 5.09, compared with the other treatments, due to the nitrification effect of ammonium. Foliar fertilizer application using NPK 10:10:10 at high concentration (1.26 % v/v) significantly improved soil available P content from 8.01 mg kg-1 to 12.27 mg kg-1, compared with the other treatments, due to drippings from the foliar sprays which improved P availability. The highest calcium nitrate fertigated pot significantly increased exchangeable Ca level in the soil from 10.20 cmolc kg-1 to 10.69 cmolc kg-1 than the other treatments. The study indicated that the highest fertigated rates of ammonium sulphate and calcium nitrate fertilizers had depressive effects on cocoa seedling growth (stem diameter, plant height, number of leaves, total leaf area, total dry matter). The study revealed that foliar application of NPK 10:10:10 at moderate and high concentrations produced seedlings with significantly higher P content than those from the other treatments